2022
DOI: 10.1002/jlb.1a0720-439r
|View full text |Cite
|
Sign up to set email alerts
|

ETS2 repressor factor (ERF) is involved in T lymphocyte maturation acting as regulator of thymocyte lineage commitment

Abstract: Thymocyte differentiation and lineage commitment is regulated by an extensive network of transcription factors and signaling molecules among which Erk plays a central role. However, Erk effectors as well as the molecular mechanisms underlying this network are not well understood. Erf is a ubiquitously expressed transcriptional repressor regulated by Erk‐dependent phosphorylation. Here, we investigated the role of Erf in T cell maturation and lineage commitment, using a double‐fluorescent Erf‐floxed mouse to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…For instance, in mice it has been shown that the TFs ELK1 and ELK4 function redundantly to restrict the generation of innate-like CD8+ T-cells [36]. Recently, Tsiomita et al showed that ERF is a potential regulator during T-lymphocyte maturation [46]. Further, for innate lymphoid cells (ILC), which are a population of lymphocytes, it can be shown that ELK3 is regulated by the circRNA circTmem241 and that the knockdown of ELK3 significantly decreased the number of ILCs [31].…”
Section: Identification Of Tfs That Are Altered By Genetic Variants M...mentioning
confidence: 99%
“…For instance, in mice it has been shown that the TFs ELK1 and ELK4 function redundantly to restrict the generation of innate-like CD8+ T-cells [36]. Recently, Tsiomita et al showed that ERF is a potential regulator during T-lymphocyte maturation [46]. Further, for innate lymphoid cells (ILC), which are a population of lymphocytes, it can be shown that ELK3 is regulated by the circRNA circTmem241 and that the knockdown of ELK3 significantly decreased the number of ILCs [31].…”
Section: Identification Of Tfs That Are Altered By Genetic Variants M...mentioning
confidence: 99%
“…For instance, in mice it has been shown that the TFs ELK1 and ELK4 function redundantly to restrict the generation of innate-like CD8+ Tcells (Maurice et al, 2018). Recently, Tsiomita et al showed that ERF is a potential regulator during T-lymphocyte maturation (Tsiomita et al, 2022). Further, for innate lymphoid cells (ILC), which are a population of lymphocytes, it can be shown that ELK3 is regulated by the circRNA circTmem241.…”
Section: Automatic Generation Of a Summary Reportmentioning
confidence: 99%